Emerging trends in disturbed function of the pancreas and dyspepsia: an Indian perspective - Rai, Ramesh Roop; Bose, Partha Pratim (International Journal of Advances in Medicine, 2024)
Disturbed function of the pancreas, especially exocrine pancreatic insufficiency (EPI) results in inadequate synthesis or delivery of the pancreatic enzyme leading to maldigestion. Due to the lack of specific symptoms and overlapping manifestations of EPI, it often goes undiagnosed and untreated. Dyspepsia is another common condition characterized by upper gastrointestinal symptoms caused by a heterogeneous group of disorders. This consensus aims at providing a comprehensive overview of the diagnosis and management of disturbed function of the pancreas and dyspepsia. A total of 95 gastroenterologists participated in expert group meetings organized via virtual focus group discussions. Recent evidence elaborating various aspects like diagnosis and management of EPI and dyspepsia, including the use of pancreatic enzyme replacement therapy (PERT) and issues with compliance were discussed. The experts emphasized that clinical symptoms of maldigestion should not be ignored, and physicians should not wait to diagnose EPI until steatorrhea occurs. Fecal elastase (FE) test and imaging should be performed to confirm diagnosis. If EPI is diagnosed or the patient experiences weight loss or steatorrhea, PERT should be initiated while ensuring compliance. Reducing pill burden, active education, monitoring, and support from healthcare programs may help ensure compliance. EPI is also a cause of dyspepsia. Further, consuming lipid-rich foods worsens symptoms of dyspepsia. First-line treatment includes dietary changes and lifestyle modifications. Digestive enzyme supplements play a significant role in alleviating symptoms of indigestion. Routine enzyme supplementation is beneficial in managing dyspepsia caused by EPI, such as, in patients with EPI due to pancreatitis or diabetes.